Hypotussic cough in persons with dysphagia: biobehavioral interventions and pathways to clinical implementation - Dallal-York, Justine; Troche, Michelle S. (Frontiers in Rehabilitation Sciences, 2024)
Cough is a powerful, protective expulsive behavior that assists in maintaining respiratory health by clearing foreign material, pathogens, and mucus from the airways. Therefore, cough is critical to survival in both health and disease. Importantly, cough protects the airways and lungs from both antegrade (e.g., food, liquid, saliva) and retrograde (e.g., bile, gastric acid) aspirate contents. Aspiration is often the result of impaired swallowing (dysphagia), which allows oral and/or gastric contents to enter the lung, especially in individuals who also have cough dysfunction (dystussia). Cough hyposensitivity, downregulation, or desensitization- collectively referred to as hypotussia- is common in individuals with dysphagia, and increases the likelihood that aspirated material will reach the lung. The consequence of hypotussia with reduced airway clearance can include respiratory tract infection, chronic inflammation, and long-term damage to the lung parenchyma. Despite the clear implications for health, the problem of managing hypotussia in individuals with dysphagia is frequently overlooked. Here, we provide an overview of the current interventions and treatment approaches for hypotussic cough. We synthesize the available literature to summarize research findings that advance our understanding of these interventions, as well as current gaps in knowledge. Further, we highlight pragmatic resources to increase awareness of hypotussic cough interventions and provide support for the clinical implementation of evidence-based treatments. In culmination, we discuss potential innovations and future directions for hypotussic cough research.